Use of Pulse Oximetry to Screen for Infant Obstructive Sleep Apnoea - Andy Cheuk-ting Hou; Eric Yat-tung Chan; Ka-li Kwok; Mei-yee Lau; Shuk-yu Leung (Pediatric Respirology and Critical Care Medicine)
Introduction: Pulse oximetry is currently used to screen for obstructive sleep apnoea (OSA) in children. However, its use in infant has not yet been well studied. Aim: The aim of this study was to develop a screening criterion using pulse oximetry to identify infant with probable OSA. Materials and Methods: This was a retrospective cross-sectional study including infants <1 year of age with features of upper airway obstruction or requiring home oxygen to find associations between obstructive apnoea hypopnoea index (OAHI) in infant polysomnography (PSG) and parameters in pulse oximetry by Spearman Rho’s correlation. The factor with the strongest correlation is further analysed by receiver-operating characteristic (ROC) curve to identify a cutoff with highest Youden index to screen for probable OSA (OAHI >2 per hour). Results: A total of 27 infants were studied. The index of oxygen desaturation with SpO2 <90% per sampled hour (ODI<90%) had the best correlation with OAHI (r = 0.52, P = 0.005). Using the cutoff of ODI<90% more than 1.3 per hour, the sensitivity and specificity for identifying OAHI >2 per hour was 77% and 71%, respectively. Conclusion: Infant pulse oximetry can be a useful tool to screen for probable infant OSA especially for paediatric units not offering infant PSG service.